2021
DOI: 10.1017/s003329172100221x
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological correlates of disorder-related autobiographical memory in anorexia nervosa

Abstract: Background Anorexia nervosa (AN) is characterized by an overgeneralization of food/body-related autobiographical memories (AM). This is regarded as an emotion regulation strategy with adverse long-term effects implicated in disorder maintenance and treatment resistance. Therefore, we aimed to examine neural correlates of food/body-related AM-recall in AN. Methods Twenty-nine female patients with AN and 30 medication-free age-sex-matched normal-weight healthy controls (HC) underwent funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 54 publications
2
21
1
Order By: Relevance
“…Natalia et al [56] reported worse performance for individuals with AN in the backwards condition of the Corsi Blocks/Spatial span and in the TMT. Similarly, Kucharska et al [73] and Terhoeven et al [58] found TMT impairments in their AN sample compared to the HC. In contrast, no significant difference emerged in the visuospatial digit span [74], spatial WM task [42] n-back or SDMT [56].…”
Section: Visuospatial Domainsmentioning
confidence: 73%
See 4 more Smart Citations
“…Natalia et al [56] reported worse performance for individuals with AN in the backwards condition of the Corsi Blocks/Spatial span and in the TMT. Similarly, Kucharska et al [73] and Terhoeven et al [58] found TMT impairments in their AN sample compared to the HC. In contrast, no significant difference emerged in the visuospatial digit span [74], spatial WM task [42] n-back or SDMT [56].…”
Section: Visuospatial Domainsmentioning
confidence: 73%
“…Performed worse than HC in 44.4% of the verbal/auditory tasks [ 59 61 ], while no difference was found in 55.6% [ 42 , 55 , 57 , 58 ] (Fig. 3 B).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations